A global decline in research productivity? Evidence from China and Germany - Philipp Böing; Paul Hünermund (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
In a recent paper, Bloom et al. (2020) find evidence for a substantial decline in research productivity in the U.S. economy during the last 40 years. In this paper, we replicate their findings for China and Germany, using detailed firm-level data spanning three decades. Our results indicate that diminishing returns in idea production are a global phenomenon, not just confined to the U.S.
Keywords: D24; E23; O31; O47; 330; Productivity; Growth; Innovation; R&D; Technological Change